Georgia : Fourth Review Under the Stand-By Arrangement and Request for Modification of Performance Criterion. (IMF Staff Country Reports; Country Report, 2009)
This paper discusses key findings of the Fourth Review Under the Stand-By Arrangement for Georgia. The strategy remains appropriate, and program targets for 2010 are in line with those presented at the Third Review. Fiscal policy will transition from an expansionary stance in 2009 to a path of strong consolidation, with a reduction in the deficit of 2u percent of GDP in 2010. Despite sizable adjustment, an external financing gap of roughly USD 400 million remains in 2010, mostly because of the slow recovery of private capital inflows.